2015
DOI: 10.3390/ani5020332
|View full text |Cite
|
Sign up to set email alerts
|

Problems Associated with the Microchip Data of Stray Dogs and Cats Entering RSPCA Queensland Shelters

Abstract: Simple SummaryMicrochip identification has become an important tool to reunite stray dogs and cats with their owners, and is now compulsory in most states of Australia. Improvement of the microchipping system in Australia is limited by a lack of published Australian data documenting the problems experienced by shelter staff when using microchip data to contact the owner of a stray animal. In this study we determine the character and frequency of inaccurate microchip data to identify weaknesses in the current m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 22 publications
1
31
1
3
Order By: Relevance
“…The national percentage reclaimed of 48% compares favorably with USA’s reports, estimated at 15% to 30% of dogs admitted to shelters [ 70 , 71 ], and is close to the United Kingdom’s 2014 pound reclaim percentage of 54% [ 72 , 73 ]. Key factors influencing the probability of a dog being reclaimed are the proportion of owned dogs with some form of identification, such as microchip, collar and tag with owner contact details, or a council registration tag [ 73 , 74 , 75 , 76 , 77 ]. However, the accuracy of the contact information is also important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The national percentage reclaimed of 48% compares favorably with USA’s reports, estimated at 15% to 30% of dogs admitted to shelters [ 70 , 71 ], and is close to the United Kingdom’s 2014 pound reclaim percentage of 54% [ 72 , 73 ]. Key factors influencing the probability of a dog being reclaimed are the proportion of owned dogs with some form of identification, such as microchip, collar and tag with owner contact details, or a council registration tag [ 73 , 74 , 75 , 76 , 77 ]. However, the accuracy of the contact information is also important.…”
Section: Discussionmentioning
confidence: 99%
“…However, the accuracy of the contact information is also important. A 2015 study found 37% of stray dogs admitted to RSPCA Queensland had inaccurate microchip data, including the chip being registered to a previous owner or organization (47%), all phone numbers disconnected or incorrect (29%) or not registered with a database (14%) [ 75 ]. The latter is illegal and the implanter must register the chip within 7 days of implantation in Queensland [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, rabbits may be less likely to be microchipped than dogs, with a recent study showing that less than a quarter of rabbit guardians, responding to an online survey, had microchipped their rabbit(s) (Oxley Previti, Alibrandi, Briefer, & Passantino, 2015). Additionally, some issues have been highlighted regarding the use of microchip data being used to reunite companion animals with guardians, such as outdated or inaccurate information (Lancaster, Rand, Collecott, & Paterson, 2015). Nevertheless, some retailers, such as Pets at Home, are taking measures to ensure rabbits are microchipped prior to purchase (RWAF, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Lancaster et al [38] found that only 28% of stray dogs were microchipped when they entered the RSPCA Queensland shelter. This may show that stray dogs are more likely to come from households who are less likely to microchip their dogs, either due to lack of knowledge, financial ability or willingness to do so.…”
Section: Microchippingmentioning
confidence: 99%
“…However, correct and updated microchip details is also crucial if microchipping is to be useful. Lancaster et al [38] reported that 37% of microchipped dogs entering the RSPCA shelter had problems with the data on the microchip, thus decreasing the chances of successful contact with owners, and subsequent reclaim, by over 20%. This indicates that programs designed to increase the accuracy of microchip data throughout an animal's life must also be explored.…”
Section: Microchippingmentioning
confidence: 99%